Platelet Count/Spleen Diameter Ratio as a Predictor of Esophageal Varices in Patients with Liver Cirrhosis - Khadka, Dipendra; KC, Sudhamshu; Khadka, Sandip; Regmi, Kiran; KC, Pooja (Journal of Nepalgunj Medical College, 2017)
Introduction: Upper gastro-intestinal endoscopy still remains the gold standard for screening of patients suspected to have esophageal varices but not without limitations. So, this study was conducted to access the diagnostic validity and correlation between non-invasive parameters like platelet count, spleen diameter and their ratio with esophageal varices (EV) in patients with liver cirrhosis. Methods: A hospital based descriptive cross-sectional study was carried out in Liver unit of National Academy of Medical Sciences, Bir Hospital, from October 2016 to September 2017. Complete blood count, liver function tests, liver ultrasound and UGI endoscopy were done for all patients included in the study to detect esophageal varices and the platelet count/spleen diameter (PC/SD) ratio was calculated and analyzed to determine whether it can predict the presence of esophageal varices or not. Results: Total patients of liver cirrhosis studied after exclusion were 191 EV was present in 125 patients (65.4%). The platelet count/spleen diameter ratio using a cutoff value of ≤ 909 to detect EV independent of the grade had 93% sensitivity and 100% specificity and positive and negative predictive values of 100% and 91% respectively. Conclusions: PC/SD ratio now can be used as a predictor of presence of esophageal varices in liver cirrhosis.